Properties of Bioplastic Straws Made from Arrowroot Starch with Chitosan Additions - Shinta Mutia Sari; Tuty Anggraini; Fauzan Azima (Institut Pertanian Bogor, 2026)
The growing environmental impact of plastic waste has sparked the development of alternative biodegradable materials. The purpose of this study is to assess the properties of bioplastic straws manufactured from arrowroot starch with various concentrations of chitosan (1%, 2%, 3%, and 4% as a strengthening agent). Arrowroot starch was used for its high amylose content (22.70%), which promotes film formation. The straws were made by blending gelatinized arrowroot starch with dissolved chitosan and glycerol as a plasticizer, then drying and shaping. The resulting bioplastic straws were tested for hardness, solubility, water absorption, biodegradability, and functional groups using FTIR and SEM. The results revealed that increasing the chitosan concentration had a substantial effect on the mechanical and functional qualities of the straws. The formulation with 3% chitosan performed the best in terms of hardness (4.11 N/cm2), moderate solubility (37.55%), excellent water absorption (41.61%), and biodegradation (79.44%). FTIR spectra revealed the interaction of hydroxyl (−OH) groups in starch with amine (−NH2) groups in chitosan, indicating a strong hydrogen bond. SEM scans revealed a tight and uniform surface structure in the 3% treatment, indicating structural integrity. The addition of chitosan effectively increased the straw's water resistance and mechanical strength. This study emphasizes the feasibility of using local agricultural resources to create ecologically friendly bioplastic straws.Keywords: arrowroot starch, biodegradability, bioplastic, chitosan, straw